Differential hypoxic response of human choroidal and retinal endothelial cells proposes tissue heterogeneity of ocular angiogenesis. (3rd June 2016) - Mammadzada, Parviz; Gudmundsson, Johann; Kvanta, Anders; André, Helder
Abstract: Purpose: To elaborate molecular differences between choroidal and retinal angiogenesis by generating and comparatively analysing human primary choroidal and retinal endothelial cell (CEC and REC) lines. Methods: Human CEC and REC were isolated by positive selection and were cultured. Characterization was performed by immunostaining for endothelial cell (EC)‐specific markers. Total RNA and protein were extracted from normoxic or hypoxic CEC and REC cultures. Quantitative polymerase chain reaction (PCR) arrays were used to comparatively analyse 133 genes between CEC and REC, and the expression differences were calculated by ΔΔ C t method. A total of 57 angiogenesis‐related protein expression differences were investigated by Western blot and proteome profiler and were calculated by densitometry. Results: Primary human CEC and REC lines stained positively for all EC markers and demonstrated high purity with similar staining and morphology. Under normoxia, CEC showed significantly lower expression levels for cell proliferation and vessel maturation genes and higher expression levels for inflammation‐related genes when compared to REC. In response to hypoxia, CEC and REC displayed differential regulation for a multitude of angiogenesis‐related genes and proteins. Furthermore, within the vascular endothelial growth factor (VEGF) family, CEC showed preferential upregulation for vascular endothelial growth factor A (VEGFA) while REC upregulated placenta growth factor (PlGF) levels. Conclusion: Differential normoxic and hypoxic regulation of angiogenesis‐related factors by CEC and REC outlines tissue heterogeneity of ocular angiogenesis and suggests that tissue specificity should be considered as a novel treatment modality for successfully overcoming choroidal and retinal angiogenic conditions in the clinic.